High pressure ammonia decomposition on Ru–K/CaO catalysts. Issue 15 (10th July 2020) - Sayas, Salvador; Morlanés, Natalia; Katikaneni, Sai P.; Harale, Aadesh; Solami, Bandar; Gascon, Jorge
Abstract : Potassium-promoted ruthenium supported on CaO is a very efficient catalyst for ammonia decomposition, surpassing the performance of other Ru-supported solids. Abstract : Potassium-promoted ruthenium supported on CaO is a very efficient catalyst for ammonia decomposition, surpassing the performance of other Ru-supported solids. At an optimum Ru loading of 3% wt, catalysts with a K/Ru atomic ratio of 0.9 showed the best catalytic performance under a wide range of operating conditions, P = 1–40 bar, T = 250–550 °C and WHSV = 9000–30 000 mL g −1 h −1 . Although NH3 conversion levels decrease considerably upon increasing the reaction pressure ( X 550 °C, 40 bar = 0.8), high pressure ammonia decomposition offers the possibility of CO x -free compressed hydrogen and hydrogen productivities and TOFs 40 times bigger than when applying atmospheric pressure. Extensive characterization by CO chemisorption and HR-TEM demonstrates that potassium promotion increases metal dispersion by decreasing the Ru particle size. Electronic effects derived from the close proximity between K and Ru result in a decrease in the reaction apparent activation energy, as shown by a detailed kinetic analysis.